Empathy and End-of-life Care in Teri Szűcs’s Memory Has Come Back to Me (2024) - Ureczky, Eszter (Magyar Gerontológia, 2024)
As a productive cultural metaphor, dementia points out the limitations implied by the notion of the human subject that has dominated Western culture’s past and history since modernity, as well as the upcoming health-related, ethical, and economic challenges of the 21st century.